Latitudinal variation in soil nematode communities under climate warming‐related range‐expanding and native plants. (20th May 2019) - Wilschut, Rutger A.; Geisen, Stefan; Martens, Henk; Kostenko, Olga; de Hollander, Mattias; ten Hooven, Freddy C.; Weser, Carolin; Snoek, L. Basten; Bloem, Janneke; Caković, Danka; Čelik, Tatjana; Koorem, Kadri; et al.
Abstract: Current climate change has led to latitudinal and altitudinal range expansions of numerous species. During such range expansions, plant species are expected to experience changes in interactions with other organisms, especially with belowground biota that have a limited dispersal capacity. Nematodes form a key component of the belowground food web as they include bacterivores, fungivores, omnivores and root herbivores. However, their community composition under climate change‐driven intracontinental range‐expanding plants has been studied almost exclusively under controlled conditions, whereas little is known about actual patterns in the field. Here, we use novel molecular sequencing techniques combined with morphological quantification in order to examine nematode communities in the rhizospheres of four range‐expanding and four congeneric native species along a 2, 000 km latitudinal transect from South‐Eastern to North‐Western Europe. We tested the hypotheses that latitudinal shifts in nematode community composition are stronger in range‐expanding plant species than in congeneric natives and that in their new range, range‐expanding plant species accumulate fewest root‐feeding nematodes. Our results show latitudinal variation in nematode community composition of both range expanders and native plant species, while operational taxonomic unit richness remained the same across ranges. Therefore, range‐expanding plant species face different nematode communities at higher latitudes, but this is also the case for widespread native plant species. Only one of the four range‐expanding plant species showed a stronger shift in nematode community composition than its congeneric native and accumulated fewer root‐feeding nematodes in its new range. We conclude that variation in nematode community composition with increasing latitude occurs for both range‐expanding and native plant species and that some range‐expanding plant species may become released from root‐feeding nematodes in the new range. Abstract : In Europe, we explored latitudinal community shifts for nematodes—abundant soil organisms that include root herbivores—in the rhizospheres of climate change‐driven range‐expanding plant species. We sampled nematode communities of several range‐expanding plant species along their expansion trajectory and compared these nematode communities with those of related plant species that are native along the entire expansion gradient. We show that nematode communities change with latitude, but that the strength of nematode community shifts strongly depends on range‐expanding plant species.